Long-Term Health Effects of the 9/11 Disaster - Brackbill, Robert M. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The terrorist attacks on the World Trade Center towers on September 11, 2001, also referred as 9/11, was an iconic event in US history that altered the global and political response to terrorism. The attacks, which involved two planes hitting the twin towers in Lower Manhattan, New York City, resulted in the collapse of the buildings and over 2800 deaths of occupants of the buildings, fire, police and other responders and persons on the street in the vicinity of the collapsing buildings. The destroyed towers and the surrounding buildings have since been replaced but the health effects that resulted from the release of tons of dust, gases and debris as well as the life threat trauma are ongoing, and represent a major health burden among persons directly exposed. Hundreds of scientific publications have documented the physical and mental health effects attributed to the disaster. The current state-of-the-art in understanding the ongoing interactions of physical and mental health, especially PTSD, and the unique mechanisms by which pollutants from the building collapse, have resulted in long term pulmonary dysfunction, course of previously reported conditions, potential emerging conditions (e.g., heart disease and autoimmune diseases), as well as quality of life, functioning and unmet health care needs would be in the purview of this Special Issue on the 9/11 Disaster.